الغش في الامتحان-الأسباب – الوسائل – الحلول المقترحة - بن علي,نوال (University of Eloued جامعة الوادي, 2023)
هدفت الدراسة إلى الكشف عن أساب الغش في الامتحانات، وأبرز الوسائل المستخدمة في الغش، وأهم الحلول المقترحة من وجه نظر الأساتذة، وبالاعتماد على المنهج الوصفي بطابعه الاستكشافي، تم إجراء الدراسة على عينة من أساتذة المراحل التعليمية الثلاث للموسم الدراسي 2022/2021، وباستخدام أدوات جمع البيانات التي تمثلت في استبيان مفتوح تم التوصل إلى النتائج التالية: 1 - أسباب الغش في الامتحان لدى التلاميذ من وجهة نظر الأساتذة هي: أسباب متعلقة ب( المتعلم، الامتحان وضروفه، العملية التعليمية والأستاذ والمنهج، وأسباب أخرى)، وأكثر أسباب الغش هي عدم التحضير الجيد للامتحان. 2- الوسائل المستخدمة للغش في الامتحان لدى التلاميذ من وجهة نظر الأساتذة هي: وسائل تقليدية ووسائل الكترونية، وأكثر الوسائل المستخدمة هي القصاصات الورقية. 3- الحلول المقترحة لمواجهة الغش في الامتحان لدى التلاميذ من وجهة نظر الأساتذة هي: حلول متعلقة بالعملية التعليمية والمتعلم، حلول متعلقة بتسيير الامتحان، وحلول أخرى، وأبرز الحلول المقترحة هي توعية التلاميذ في مختلف الجوانب. Abstract: The study aimed to reveal the causes of cheating in exams, the most prominent methods used in it, and the most important proposed solutions from the teachers’ point of view, and based on the descriptive approach in its exploratory nature, the study was conducted on a sample of teachers from the three educational stages for the academic season 2021/2022, and using data collection tools Which was represented in an open questionnaire, the following results were reached: 1 - The reasons for cheating in the exam among the students from the point of view of the teachers are: reasons related to (the learner, the exam and its conditions, the educational process, the teacher and the curriculum, and other reasons), and the most common reason for cheating is the lack of good preparation for the exam. 2- The methods used for cheating in the exam among students from the point of view of teachers are: traditional means and electronic means, and the most used means are paper clips. 3- The proposed solutions to confront cheating in the exam among students from the point of view of the teachers are: solutions related to the educational process and the learner, solutions related to the conduct of the exam, and other solutions, and the most prominent proposed solutions is educating students in various aspects.
من وجهة نظر الأساتذة
Keywords: غش; امتحان